2013
DOI: 10.1021/cg4014575
|View full text |Cite
|
Sign up to set email alerts
|

Novel Three-Dimensional Organic–Inorganic Heterometallic Hybrid Built by Sandwich-Type Tetra-Mn-Substituted Germanotungstates through Mixed 3d and 4f Metal Linkers

Abstract: The reaction of trivacant Keegin germanotungstate [A-α-GeW9O34]10– with Mn2+ and Ce4+ cations in the presence of oxalate ligand under hydrothermal conditions led to the isolation of a novel organic–inorganic hybrid 3d–4f heterometallic germanotungstate K4Na4[Ce2(ox)3(H2O)2]2{[Mn(H2O)3]2[Mn4(GeW9O34)2(H2O)2]·14H2O (1) (ox = oxalate), which has been characterized by elemental analysis, IR spectroscopy, thermogravimetric (TG) analysis, and single-crystal X-ray crystallography. Interestingly, each tetra-MnII-subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…31,32 In view of diverse POMs, 33 sandwich-type POMs are usually synthesized in weak acidic solutions, which may show synergistic effects with combined transitional metal ions and intriguing redox properties. [34][35][36][37][38][39][40] Wang et al recently reported tetranuclear zirconiumsubstituted polyoxometalates with peroxidase-like activity, which indicates that the active catalytic species are ascribed to the unique structural feature of sandwiched {Zr 4 } clusters but not the lacunary polyoxometalate anions themselves or the independent Zr ions. 41 However, the reaction time of TMB oxidation in Wang's work was 90 min, which still did not fulll the stringent requirement of bio-detectors, requiring a fast response.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 In view of diverse POMs, 33 sandwich-type POMs are usually synthesized in weak acidic solutions, which may show synergistic effects with combined transitional metal ions and intriguing redox properties. [34][35][36][37][38][39][40] Wang et al recently reported tetranuclear zirconiumsubstituted polyoxometalates with peroxidase-like activity, which indicates that the active catalytic species are ascribed to the unique structural feature of sandwiched {Zr 4 } clusters but not the lacunary polyoxometalate anions themselves or the independent Zr ions. 41 However, the reaction time of TMB oxidation in Wang's work was 90 min, which still did not fulll the stringent requirement of bio-detectors, requiring a fast response.…”
Section: Introductionmentioning
confidence: 99%
“…Design and synthesize of organic-inorganic hybrids have attracted a great deal of interest in the chemistry and materials fields, not only because of their fascinating topology and intriguing architectures, [1][2][3][4] but also due to their potential applications in magnetism, [5][6][7][8][9] luminescence, [10][11][12][13][14][15][16] ion exchange, [17,18] and catalysis [19] etc. Among them, octamolybdate [Mo 8 O 26 ] 4-based polyoxometalates (POMs) have been extensively studied for their structural diversity and potential coordination capability in building high dimensional frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Because of high affinity of RE cation linkers to the anionic surface of polyanions, their utilization in synthesis is challenging and almost leads to precipitation [ 180 , 181 ]. By introducing O-donor ligands to the reaction medium Zhao et al [ 182 ] successfully established the 3D K 4 Na 4 [Ce 2 (ox) 3 (H 2 O) 2 ] 2 {[Mn(H 2 O) 3 ] 2 [Mn 4 (GeW 9 O 34 ) 2 (H 2 O) 2 ]·14H 2 O hybrid with Weakley sandwich-type structure via tetra Mn II belt and 3d-4f connector. Zhang and co-workers prepared two types of RESP hybrids based on phosphotungstates via oxalate linkages.…”
Section: Inorganic–organic Hybrids Based On Pbtrehdsmentioning
confidence: 99%